2018
DOI: 10.1080/17450101.2018.1449785
|View full text |Cite
|
Sign up to set email alerts
|

Between the village and the global city: the production and decay of translocal spaces of Thai migrant workers in Singapore

Abstract: This paper explores the mobilities and structural moorings of Thai labour migrants in Singapore from a translocal perspective. We argue that combining the mobilities paradigm with the concept of translocality offers a fruitful avenue of investigation not only of the production of translocal spaces, but also of their temporality and mutability. Through a multi-sited research approach we shed light on the genesis as well as the decay of translocal connections. This paper shows that translocal structures are impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 45 publications
1
23
0
1
Order By: Relevance
“…At the same time, increasing variability in rainfall patterns in Northeast Thailand is placing stress on agricultural productivity, thereby increasing the need to adapt and explore alternative agricultural crops and practices (Mikhail et al 2010; Naruchaikusol 2016; Choenkwan and Fisher 2018). Typical of Northeast Thailand, internal and international labor migration is a major livelihood strategy in Ban Chai, resulting in increasing translocal connectedness and multi-sited household footprints (Rigg and Salamanca 2011;Peth et al 2018;Porst and Sakdapolrak 2018). With its exposure to climate change, its high rate of migration and the rapid change of its agricultural systems, the sub-district of Ban Chai provides a good example for studying the role of translocal networks in agricultural innovation.…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, increasing variability in rainfall patterns in Northeast Thailand is placing stress on agricultural productivity, thereby increasing the need to adapt and explore alternative agricultural crops and practices (Mikhail et al 2010; Naruchaikusol 2016; Choenkwan and Fisher 2018). Typical of Northeast Thailand, internal and international labor migration is a major livelihood strategy in Ban Chai, resulting in increasing translocal connectedness and multi-sited household footprints (Rigg and Salamanca 2011;Peth et al 2018;Porst and Sakdapolrak 2018). With its exposure to climate change, its high rate of migration and the rapid change of its agricultural systems, the sub-district of Ban Chai provides a good example for studying the role of translocal networks in agricultural innovation.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Understanding why particular changes are more likely to be facilitated through migration-related knowledge transfers also requires considering the kind of knowledge migrants acquire during migration and its applicability to rural livelihoods. As the majority of migrants from Northeast Thailand work in in the construction sector or in factories in the metropolitan areas of Thailand or abroad (Peth et al 2018;Porst and Sakdapolrak 2018), they are unlikely to gain knowledge about different agro-ecological environments during migration (Isaac et al 2014;Matous and Todo 2018). Even in the case of migrants working in modern agriculture, e.g.…”
Section: Intensification Versus Extensification: Viability Of Migratimentioning
confidence: 99%
“…The majority of participants interviewed spent more than 10 years abroad, and went not only to one country but also to at least two or three other work destinations. Despite these long migration periods, and due to social segregation which migrants often face at their place of destination, they maintain strong translocal connections to their places of origin (Peth et al, 2018). They focus their hard-working lives abroad on their livelihoods back home: the origin becomes the destination.…”
Section: When the Origin Becomes The Destinationmentioning
confidence: 99%
“…Social embeddedness at the destination also has an impact on the acquisition of social remittances. In the case of Thai workers in Singapore, we found that the migration system and immigration policies create a state of structural segregation, limiting contact and exchange between migrants and the host society (cf., Peth et al, 2018). For the acquisition of social remittances in terms of social capital, new ideas, and changing identities, this means that Thai workers in Singapore have little exchange with people other than their colleagues and fellow migrants.…”
Section: Social Remittances Within a Translocal Settingmentioning
confidence: 99%
“…These emerging social forms have been foregrounded by the existing literature on translocality (see Greiner and Sakdapolrak 2013; Nguyen and Locke 2014; Oakes and Schein 2006; Peth et al . 2018). Translocal mobility potentially alleviates and engenders precarity.…”
Section: Whither Precarity? Contextualising and Temporalising A Fashimentioning
confidence: 99%